Self competence and psychological hardiness: self-efficacy as Moderator - Mihaela Rus; Mihaela Luminita Sandu; Senouci Boumediene; Tănase Tasențe; Djellouli Zineb (Technium Social Sciences Journal, 2020)
The study aimed to determine the role that self-efficacy play between self-competence and psychological hardiness, The study sample consists of (278) indivudial who chosen from two countries, and to achieve the objectives of the study the researchers use psychological hardiness scale, self-efficacy scale, self-competence scale, after collecting and processing information statistically using the Statistical Package for Social Sciences SPSS, the researchers reached the following results: that self-efficacy don’t play moderator role between self-competence and psychological hardiness. self-efficacy effect in psychological hardiness and not effect in self competence. there is no difrrent significant in self efficacy according to interaction between age and gender.